Magnesium Technology 2012 - Mathaudhu, Suveen; Sillekens, Wim.; Neelameggham, Neale; Hort, Norbert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The Magnesium Technology Symposium, which takes place every year at the TMS Annual Meeting & Exhibition, is one of the largest yearly gatherings of magnesium specialists in the world. Papers are presented in all aspects of the field, ranging from primary production to applications to recycling. Moreover, papers explore everything from basic research findings to industrialization. Magnesium Technology 2011 covers a broad spectrum of current topics, including alloys and their properties; cast products and processing; wrought products and processing; forming, joining, and machining; corrosion and surface finishing; ecology; and structural applications. In addition, you'll find coverage of new and emerging applications in such areas as biomedicine and hydrogen storage.
Keywords: Metals; Coatings; Tribology; Corrosion and anti-corrosives.; Materials; Metals and Alloys; Coatings; Tribology; Corrosion; Materials Engineering